trans Fatty Acid Contents of Crude Soybean Oils Industrially Obtained by Solvent Extraction with Hexane - YILMAM, LUTFI; TASAN, MURAT (Asian Journal of Chemistry, 2010)
The trans fatty acid contents of crude soybean oils, industrially obtained by using continuous solvent (hexane) extraction processes, were determined by capillary gas-liquid chromatography. According to the analysis results, the contents of total trans fatty acid were within the ranges of 0.05 ± 0.02- 0.17 ± 0.05 % of total fatty acids. The total C18:2 trans and total C18:3 trans acids were found in all the analyzed samples. The contents of these trans fatty acids were 0.01 ± 0.00-0.06 ± 0.02 and 0.02 ± 0.01-0.09 ± 0.04 %, respectively. As for the total C18:1 trans acid, its levels were present is less than 0.02 ± 0.02 % of total fatty acids. Also, no total C18:1 trans acid was found in some samples. The trans fatty acids were probably formed by heat treatment of soybeans before or during the solvent extraction processes. Although very low values of the trans fatty acids were found in the crude soybean oils, the presence of these fatty acids can be caused difficulties to produce refined soybean oils with or without low level of trans fatty acid.